2015
DOI: 10.1371/journal.pone.0132378
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Microgravity Exerts an Age-Dependent Effect on the Differentiation of Cardiovascular Progenitors Isolated from the Human Heart

Abstract: Microgravity has a profound effect on cardiovascular function, however, little is known about the impact of microgravity on progenitors that reside within the heart. We investigated the effect of simulated microgravity exposure on progenitors isolated from the neonatal and adult human heart by quantifying changes in functional parameters, gene expression and protein levels after 6-7 days of 2D clinorotation. Utilization of neonatal and adult cardiovascular progenitors in ground-based studies has provided novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 65 publications
(69 reference statements)
1
26
1
Order By: Relevance
“…Recent research in our own laboratory has shown that neonatal human CPCs cultured under two-dimensional (2D) clinorotation, which approximates weightlessness by rotating the cell culture vessel about a horizontal axis, exhibit increased expression of markers of early cardiovascular development and pluripotency (i.e., MESP1 , T (Brachyury), and OCT4 ) as well as broad changes to microRNA expression. 1 The changes in microRNA expression experienced by CPCs in these experiments mirrored the expression of similar microRNAs in human embryonic stem cells (ESC) under normal conditions of early cardiovascular development, thereby suggesting that such culture conditions induce an epigenetic environment that favors an earlier development status. Such a state appears increasingly beneficial for cardiovascular repair.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Recent research in our own laboratory has shown that neonatal human CPCs cultured under two-dimensional (2D) clinorotation, which approximates weightlessness by rotating the cell culture vessel about a horizontal axis, exhibit increased expression of markers of early cardiovascular development and pluripotency (i.e., MESP1 , T (Brachyury), and OCT4 ) as well as broad changes to microRNA expression. 1 The changes in microRNA expression experienced by CPCs in these experiments mirrored the expression of similar microRNAs in human embryonic stem cells (ESC) under normal conditions of early cardiovascular development, thereby suggesting that such culture conditions induce an epigenetic environment that favors an earlier development status. Such a state appears increasingly beneficial for cardiovascular repair.…”
Section: Introductionmentioning
confidence: 70%
“…MicroRNA array profiling was performed as previously described. 1 Briefly, the miScript II RT Kit (Qiagen, Valencia, CA) was used to convert 500 ng of total RNA into cDNA, which was diluted, added to miScript SYBR Green PCR master mix and 10× universal primer mix (Qiagen, Valencia, CA), and run on human development and differentiation miScript plates (MIHS-103ZA; Qiagen, Valencia, CA). Fold changes were determined for each clone using the Qiagen Data Analysis Center ( http://www.qiagen.com/us/shop/genes-and-pathways/data-analysis-center-overview-page/ ) using all available housekeeping genes.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of simulated microgravity on cells is known to vary depending on factors including cell type, specific bioreactor used and duration of exposure to simulated microgravity 40 41 42 . Our study suggests that a short-term exposure of cardiac progenitors to simulated microgravity in an RPM may be leveraged to improve the expansion and viability of cardiac progenitors and subsequent generation of CMs.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, up-regulation of heat shock proteins was also observed in rat hypothalamus tissues 45 , the Jurkat cells 46 and myelomonocytic U937 cells 47 as a result of exposure to microgravity, and BIRC5 was up-regulated in thymus after mice returned from a spaceflight 48 . In addition, a study on neonatal and adult cardiovascular progenitors reported that simulated microgravity could affect cell differently depending on age 42 . Among many differential responses, final number of cells and expression of DNA repair genes were increased in neonatal but not adult cardiac progenitors upon exposure to simulated microgravity 42 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation